A case in which the ileocolic vein draining into the gastrocolic trunk of Henle could be diagnosed preoperatively: a rare anatomical case report - Rie Mizumoto; Mitsuyoshi Tei; Soichiro Mori; Kentaro Nishida; Akinobu Yasuyama; Masatoshi Nomura; Yukihiro Yoshikawa; Toshinori Sueda; Tae Matsumura; Chikato Koga; Hiromichi Miyagaki; Masanori Tsujie; et al. (Surgical Case Reports, 2022)
Abstract Background Numerous variations in vascular anatomy have been reported in the right colon. The ileocolic vein (ICV) generally drains directly into the superior mesenteric vein (SMV), and is an important landmark for laparoscopic surgery in right colon cancer. We present here a patient with a vascular anomaly of the ICV that was diagnosed on preoperative imaging. Case presentation A 65-year-old woman was diagnosed with transverse colon cancer by colonoscopy. Preoperative computed tomography scan showed that the ICV drained into the gastrocolic trunk of Henle (GCT) rather than the SMV. Single-incision laparoscopic transverse colectomy with D3 lymph node dissection was performed, dividing the middle colic vein (MCV) and preserving the right gastroepiploic vein (RGEV), anterior superior pancreaticoduodenal vein (ASPDV), GCT and ICV. The intraoperatively identified venous anatomy was consistent with the preoperative evaluation, and the RGEV, ASPDV and ICV were found to form the GCT. Conclusion We report a rare vascular anatomical anomaly that was diagnosed preoperatively, facilitating safe and successful single-incision laparoscopic surgery with D3 lymph node dissection.